Współpraca krajów RWPG w zaopatrzeniu w drewno, wyroby drzewne i celulozowo-papiernicze - Puchalski, Tadeusz (Wydział Prawa i Administracji UAM, 1974)
The author comes to the conclusion that there is a very uneven distribution of sources of raw materials in the CMEA countries and that is why the foreign trade of wood, woodwork and cellulose-paper products among these countries is highly developed. The CMEA countries as a whole have some surplus of wood raw miaterial (with the exception of brioadleaved logs), woodwork and news-print. On the other hand, cellulose and other paper and board lines are in short supply in spite of a constant and marked increase in output.
The Cooperation of CMEA Countries in Supply with Wood, Woodwork and Cellulose-Paper Products